Gender Differences in Transdiagnostic Predictors of Problematic Alcohol Consumption in a Large Sample of College Students in Ecuador - Sánchez-Puertas, Rafael; Ruisoto, Pablo; López-Núñez, Carla; Vaca-Gallegos, Silvia (Frontiers in Psychology, 2022)
Background: Alcohol use is one of the main risk factors that leads to detrimental health effects and support for a transdiagnostic approach to alcohol use disorders is growing. However, the role of transdiagnostic predictors of problematic alcohol consumption in Ecuador are understudied. Objective: The aim of this study was to examine gender differences in psychological stress and inflexibility as transdiagnostic predictors of problematic alcohol consumption in a large sample of college students in Ecuador. Methods: A total of 7,905 college students (21.49 years, SD = 3.68; 53.75% females) were surveyed using the following standardized scales: Alcohol Use Disorders Identification Test (AUDIT), Perceived Stress Scale (PSS-14), and Acceptance and Action Questionnaire (AAQ-7). Macro Process for SPSS (models 4 and 7) was used to analyze mediation and moderation effects. Results: Reported alcohol consumption was significantly higher in men than women students. On the other hand, women reported significantly higher levels of perceived stress and psychological inflexibility than men students. Gender, age, psychological stress and inflexibility were significant predictors of alcohol consumption. Moreover, psychological inflexibility mediated the impact of stress on alcohol consumption, particularly in women (for men b = .065, 95% CI [.048 to .083], for women b = .070, 95% CI [.051 to .089]). Discussion: Results of this study support psychological stress and psychological inflexibility as critical transdiagnostic variables related to increased rates of alcohol consumption among Ecuadorian college students. These conclusions contribute to the development of transdiagnostic comprehensive programs, which encompasses promotive, preventive and treatment services that allow to alleviate the burden of alcohol, as well as to enrich the growing research on alcohol consumption in this population from a gender perspective.